Role of Penicillin-Binding Proteins in the Initiation of the AmpC β-Lactamase Expression in Enterobacter cloacae - Pfeifle, Dieter (American Society for Microbiology, 2000)
Penicillin-binding proteins (PBPs) are involved in the regulation of β-lactamase expression by determining the level of anhydromuramylpeptides in the periplasmatic space. It was hypothesized that one or more PBPs act as a sensor in the β-lactamase induction pathway. We have performed induction studies with Escherichia coli mutants lacking one to four PBPs with dd-carboxypeptidase activity. Therefore, we conclude that a strong β-lactamase inducer must inhibit all dd-carboxypeptidases as well as the essential PBPs 1a, 1b, and/or 2.